Monetary and fiscal complementarity in the Covid-19 pandemic - Jagjit Chadha; Luisa Corrado; Jack Meaning; Tobias Schuler (European Central Bank (ECB), 2021)
In response to the coronavirus (Covid-19) pandemic, there has been a complementary approach to monetary and fiscal policy in the United States with the Federal Reserve System purchasing extraordinary quantities of securities and the government running a deficit of some 17% of projected GDP. The Federal Reserve pushed the discount rate close to zero and stabilised financial markets with emergency liquidity provided through a new open-ended long-term asset purchase programme. To capture the interventions, we develop a model in which the central bank uses reserves to buy much of the huge issuance of government bonds and this offsets the impact of shutdowns and lockdowns in the real economy. We show that these actions reduced lending costs and amplified the impact of supportive fiscal policies. We then run a counterfactual analysis which suggests that if the Federal Reserve had not intervened to such a degree, the economy may have experienced a significantly deeper contraction as a result from the Covid-19 pandemic.
Keywords: 330; Covid-19; monetary-fiscal interaction; non-conventional monetary policy; quantitative easing